(untitled) (Jurnal Ilmiah Psikologi MIND SET, 2023)
In Indonesia, the Phi generation has a reputation for being disloyal employees who quickly leave their jobs. However, this generation is becoming the dominant population in Indonesia and is starting to fill the job market. This phenomenon raises questions for researchers about the psychological resilience or hardiness of this generation. The study surveyed 156 employees born between 1989-2000 who worked in various private and state-owned companies. The DRS-II scale (18 items, α = 0.82) and additional questions were used to collect data. Results showed that 21.2% of participants had very high hardiness, 52.6% had high hardiness, 24.4% had moderate hardiness, and 1.9% had low hardiness. Members of this generation generally did not show any differences in average hardiness in several demographic categories, except for the position level group. The control dimension had the highest mean score, which participants attributed to their strategies for managing time, work, and priorities.